Exploring English Vocabulary Mastery Through Watching Movie: A Descriptive Qualitative Design - Sri Rezky Arif; Riny Jefri; Indrawaty Asfah (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
This study aims to find out whether the application of film as a learning medium can improve the English vocabulary skills of the subjects. The subjects of this study were students of the Bahasa Inggris D4 or commonly called Business English Communication study program class of 2020. The sample consisted of 30 students from class A and B. In carrying out this study, data was obtained by giving 2 tests and treatment. The treatment in question is watching a movie called The Founder. The results of the study show that the 2020 students' Business English Communication vocabulary skills are still lacking . This can be seen from the results of test 1 which only obtained an average result of 69.7 while test 2 was 62.8 and the use of film as a learning medium. still has a small impact on the vocabulary mastery of Business English Communication 2020 students. Based on the findings above, the researcher concludes that the use of film as a learning medium does not have a major impact on the vocabulary of Business English Communication 2020 students because it can be seen from the low test results they obtained.Keywords: English, Vocabulary Mastery, Impact, Movie